Perceived Risk and Consumer Buying Behavior for E-Commerce in Malaysia - Tan, Tzyy Tsong (2011)
Today, in modern society, e-commerce provides the latest information service platform for enterprises in all sectors of the wide open-spaced market. In Malaysia, the practice of e-business enterprises has begun on some scale and compared with other countries, Malaysia e-commerce is still not matured. “Lifestyle” is a very mysterious word. It is also known as the living condition, from a marketing point of view on what time is vital from the creation of a homogeneous product to the consumer acceptance of the concept. The main purpose of this paper is to study how consumers’ lifestyle affect the consumer buying behavior in Malaysia’s e-commerce, and try some measures proposed in order to understand and analyse a variety of factors: “perceived risk, consumer lifestyles, innovation and other factors linked.” From the data analysis of the online survey of 300 consumers who had completed the online purchase, the results shows that consumers who have a more price oriented lifestyle would be aware of the lower risks in e-commerce. In addition, consumers who have a more net oriented lifestyle will purchase more through e-commerce than consumers who have a less net oriented lifestyle.